Tindak Tutur Memerintah dalam Bahasa Bugis di Desa Sungai Tawar Tanjung Jabung Timur: Imperative Speech Acts in the Bugis Language in the Village of Sungai Tawar, East Tanjung Jabun - Kasmi Hedrianti; Akhyaruddin Akhyaruddin; Priyanto Priyanto (Universitas Tidar, 2026)
This study aims to determine the forms of commanding speech acts in the Bugis language in Sungai Tawar Village, East Tanjung Jabung Regency. This study uses a pragmatic approach with a descriptive qualitative approach. The data for this study consist of Bugis speech acts of the Sungai Tawar Village community, which are still actively used in everyday communication. In the data collection process, the researcher used several techniques, namely listening, note-taking, recording, and engaging in conversation, in the daily conversations of the Sungai Tawar Village community. The results indicate two forms of commanding speech acts in the Bugis language: direct speech acts (11 utterances) and indirect speech acts (5 utterances). The use of direct (explicit) commanding speech acts includes two utterances of requesting, one utterance of requesting, one utterance of prohibiting, one utterance of permitting, one utterance of suggesting, one utterance of recommending, one utterance of expecting, one utterance of proposing a choice, one utterance of inviting, one utterance of inviting, and two utterances of urging. Furthermore, the use of indirect (implicit) strategies was found in five utterances: 1 prohibition, 1 command, 1 request for assistance, 1 appeal/urgency, and 1 request/excuse me. These findings confirm that the use of commanding speech acts in Bugis not only reflects the linguistic function of commands but also reflects the social values, politeness, and cultural norms of the community. This research is expected to contribute to the preservation of regional languages ​​while enriching the study of pragmatics in the local realm.